Schoolteachers' experiences of implementing school-based vaccination programs against human papillomavirus in a Chinese community: a qualitative study - Judy Yuen-man Siu; Albert Lee; Paul K. S. Chan (BMC, 2019)
Abstract Background Cervical cancer was the fourth most common cancer among women worldwide in 2012 and was the eighth most common cancer in 2014 and the eighth greatest cause of female cancer deaths in Hong Kong in 2015. Human papillomavirus (HPV) vaccination has been clinically documented to have a high efficacy in reducing HPV-related cervical intraepithelial neoplasia incidence. Therefore, receiving vaccination is a crucial public health measure to reduce disease burden. Significant others, such as schools and schoolteachers, have prominent influence in shaping adolescents' health perceptions and behavior. Therefore, the perspective of schools and schoolteachers regarding vaccination can significantly influence students' acceptance and accessibility of the vaccine. However, few studies have analyzed the perceptions of schoolteachers toward HPV vaccination, and even fewer have concerned how schoolteachers' perceptions influence their schools' motivation in implementing school-based HPV vaccination programs. This study was thus conducted to fill this literature gap. Methods With a Chinese community as the field site of this study, a qualitative approach of five focus group interviews was conducted with 35 schoolteachers from five primary and eight secondary schools in Hong Kong between July 2014 and January 2015. Thematic content analysis was used for data analysis. Results Perceptual, institutional, student and parental, and collaborator barriers interacted to discourage the sampled schoolteachers from organizing school-based HPV vaccination programs. Lack of knowledge regarding HPV vaccination, perception of HPV vaccination as inappropriate given the students' age, violation of traditional cultural values, lack of perceived needs and perceived risk, opposition from schools, low priority of HPV vaccination over other health education topics, lack of government support, lack of interest from parents and students, and lack of confidence in implementing organizations, all were the mentioned barriers. Conclusions The sampled schoolteachers were demotivated to organize school-based HPV vaccination programs because of their perceptions and various social and cultural factors. As significant influencers of adolescent students, schoolteachers and schools should receive more support and information on organizing school-based HPV vaccination programs in the future.